1991
DOI: 10.1002/1097-0142(19911015)68:8<1691::aid-cncr2820680805>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The use of prophylactic eye drops during high-dose cytosine arabinoside therapy

Abstract: An ocular toxic reaction presenting as conjunctivitis or keratitis develops in a significant number of patients who are treated with high‐dose cytosine arabinoside (ara‐C). Although eye drops containing glucocorticoid reportedly decrease the incidence, they do not totally eliminate this side effect. In comparing this technique with artificial tears, both were found to be equally effective. The primary mechanism by which eye drops decrease ocular toxic reactions associated with high‐dose ara‐C is presumably due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…13 The possible mechanism for this frequent and vigorous application of eye drops in preventing cytarabineinduced ocular toxicity is the dilution of cytarabine excreted onto the surface of eyes. 13 Another possible explanation for the reduced efficacy of topical corticosteroid in preventing kerato-conjunctivitis observed in the present study is the difference in the topical corticosteroid used (0.1% betamethasone) as compared with those in other studies (1% prednisolone or 0.1% dexamethasone). 1,3,12,13 Further, the frequency of administration differs among the studies.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…13 The possible mechanism for this frequent and vigorous application of eye drops in preventing cytarabineinduced ocular toxicity is the dilution of cytarabine excreted onto the surface of eyes. 13 Another possible explanation for the reduced efficacy of topical corticosteroid in preventing kerato-conjunctivitis observed in the present study is the difference in the topical corticosteroid used (0.1% betamethasone) as compared with those in other studies (1% prednisolone or 0.1% dexamethasone). 1,3,12,13 Further, the frequency of administration differs among the studies.…”
Section: Discussionmentioning
confidence: 79%
“…Another promising prophylaxis is frequent and vigorous application of eye drops with artificial tears (two drops, every 4 h), which was also shown as effective as topical corticosteroid in preventing cytarabine-induced corneal toxicity. 13 The possible mechanism for this frequent and vigorous application of eye drops in preventing cytarabineinduced ocular toxicity is the dilution of cytarabine excreted onto the surface of eyes. 13 Another possible explanation for the reduced efficacy of topical corticosteroid in preventing kerato-conjunctivitis observed in the present study is the difference in the topical corticosteroid used (0.1% betamethasone) as compared with those in other studies (1% prednisolone or 0.1% dexamethasone).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjunctivitis and keratitis are very common and usually appear on days 6-8 of the treatment, unless prophylactic treatment with saline or corticosteroid eye drops are given [6]. Slit lamp examination typically demonstrates corneal microcysts and punctate epithelial erosions.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown topical prednisolone 1% to be more effective than placebo, 8 others report that artificial tears are equally effective. 9 This gives further credence to the theory that dilution plays an important role in reducing toxicity. Some reports prefer dexamethasone to prednisolone due to a 5-to 7-fold higher anti-inflammatory activity and a greater capacity to penetrate the lipid-rich corneal epithelium.…”
mentioning
confidence: 99%